Utilisation of Online Public Access Catalogue (OPAC) among Students of Federal University of Agriculture, Abeokuta, Nigeria - Abayomi, Owolabi Kehinde; Susan, Adeyeye Yemisi; S.S, Musa.; Dolapo, Pelemo Grace; Oluronke, Adesina A (Gyan Management Journal, 2022)
Libraries house information in various forms such as prints and non-print materials. Considering the avail ability of various resources in the library, there is need for information retrieval systems that will enable users to have access to required information as at when needed. Modern libraries are increasingly being rede fined to provide unrestricted access to information in various sources and formats. Academic libraries differ from one another in many respects, but they all have the same basic function, which is to aid the parent institu tion to carry out its objectives in the areas of teaching, learning, and community development. Libraries con tribute to the realisation of these objectives and support